Recent development on bio‐based thermosetting resins. Issue 14 (5th June 2021) - Liu, Jingkai; Zhang, Liyue; Shun, Wuliuyi; Dai, Jinyue; Peng, Yunyan; Liu, Xiaoqing
Abstract: Due to the rapid depletion of crude oil and serious environmental pollution, the synthesis of polymers from renewable resource is becoming more and more important. Up to now, a great variety of biomass and bio‐based platform compounds have been taken to prepare the polymers. However, as two representative thermosetting resins, epoxy and benzoxazine resin derived from renewable feedstocks only obtain limited attention compared with the popular bio‐based plastics, including PLA, PBAT and PHBV etc. The reason might be that the properties of previously reported thermosetting resins directly obtained from biomass are usually unsatisfied, and their application fields are limited. In this paper, the latest development on the synthesis of high‐performance bio‐based epoxy and polybenzoxazine resins are reviewed. In addition, to further broaden their applications, the functionalization strategies are also summarized. The objective of this work is to help us fully aware the present situation of bio‐based thermosetting resins and then promote their faster development, especially practical application. Abstract :